Antimicrobial Peptides: Bringing Solution to the Rising Threats of Antimicrobial Resistance in Livestock - Saeed, Shamsaldeen Ibrahim; Mergani, AhmedElmontaser; Aklilu, Erkihun; Kamaruzzaman, Nor Fadhilah (Frontiers in Veterinary Science, 2022)
Antimicrobial therapy is the most applied method for treating and preventing bacterial infection in livestock. However, it becomes less effective due to the development of antimicrobial resistance (AMR). Therefore, there is an urgent need to find new antimicrobials to reduce the rising rate of AMR. Recently, antimicrobial peptides (AMPs) have been receiving increasing attention due to their broad-spectrum antimicrobial activity, rapid killing activities, less toxicity, and cell selectivity. These features make them potent and potential alternative antimicrobials to be used in animals. Here, we discuss and summarize the AMPs in animals, classification, structures, mechanisms of action, and their potential use as novel therapeutic alternative antimicrobials to tackle the growing AMR threat.